PENINGKATAN KEMAMPUAN BERPIKIR KRITIS MELALUI METODE EKSPERIMEN BERBASIS LINGKUNGAN: (Penelitian Tindakan di Kelompok B PAUD Mentari, Kab. Bengkulu Selatan, Tahun 2014/ 2015) - ANGGREANI, CHRESTY (JPUD - Jurnal Pendidikan Usia Dini, 2017)
Abstract: The aim of this research is to improving critical thinking abilty in group B PAUD Mentari, Kab Bengkulu Selatan. The research used ation research method according to Kemmis and Taggart were conducted over 14 meetings. Teh subject of this research is gruop B PAUD Mentari which is consist about 10 children’s where consist of 5 male and 5 female. The steps of the action research method of Kemmis and Taggart models that include: (1) planning, (2) action, (3) observation, and (4) reflection. The data collected by observation, documentation with data analysis by quantitative and qualitative. Qualitative data analysis is used mode analysis by Miles and Huberman.Before conducting the research, pre-action research conducted to determine the percentage of the initial result of the critical thinking of children. The result of research says that the average grade in the pre-action amounted to 40,27% After the action in the first cycle increased the average grade o 56,03% and became the second cycle increased to 88,48%. The result of this research shows that critical thinking abilty can be improved through experiment method, proven by the result of the observation which did it and had reach success indicator about 71%. Keywords: Critical Thinking, Experiment Method, Action Research